SIFAT MANUSIA DAN ANTROPOLOGI KRISTEN: PERSPEKTIF FILSAFAT TENTANG HAKIKAT KEMANUSIAAN: Sifat Manusia; Antropologi Kristen; Perspektif Filsafat; Hakikat Kemanusiaan. - Saleleubaja, Junardi; Astuti, Dewi (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
This article discusses human nature and Christian anthropology from a philosophical perspective in the context of understanding the nature of humanity. The background of this research is the need for a deep understanding of human nature and Christian anthropology to face moral challenges in today's society. The purpose of this study is to analyze the philosophical view of human nature and the understanding of Christian anthropology, as well as its implications for our understanding of the nature of humanity. The research method used is a descriptive qualitative method with a library search approach to relevant philosophical and theological sources. The results of this study show that concepts such as rationality, dignity, and human responsibility have an important role in understanding the nature of humanity. The conclusion of this article is that philosophical thought and Christian anthropology complement each other in forming a comprehensive understanding of human nature and humanity.